3D analysis of the MT data for resistivity structure beneath the Ashute geothermal site, Central Main Ethiopian Rift (CMER) - Aklilu Abossie; Shimeles Fisseha; Bekele Abebe (Heliyon, 2023)
The Ashute geothermal field (around Butajira) is located near the western rift escarpment of the Central Main Ethiopian Rift (CMER), about 5–10 km west of the axial part of the Silti Debre Zeit fault zone (SDFZ). Several active volcanoes and caldera edifices are hosted in the CMER. Most of the geothermal occurrences in the region are often associated with these active volcanoes. The magnetotelluric (MT) method has become the most widely used geophysical technique for the characterization of geothermal systems. It enables the determination of the subsurface electrical resistivity distribution at depth. The high resistivity under the conductive clay products of hydrothermal alteration related to the geothermal reservoir is the main target in the geothermal system. The subsurface electrical structure of the Ashute geothermal site was analyzed using the 3D inversion model of MT data, and the results are endorsed in this work. The ModEM inversion code was used to recover the 3D model of subsurface electrical resistivity distribution. According to the 3D inversion resistivity model, the subsurface directly beneath the Ashute geothermal site can be represented by three major geoelectric horizons. On top, a relatively thin resistive layer (>100 Ωm) represents the unaltered volcanic rocks at shallow depths. This is underlain by a conductive body (< 10 Ωm), possibly associated with the presence of clay horizon (smectite and illite/chlorite zones), resulting from the alteration of volcanic rocks within the shallow subsurface. In the third bottom geoelectric layer, the subsurface electrical resistivity gradually increases to an intermediate range (10–46 Ωm). This could be related to the formation of high-temperature alteration minerals such as chlorite and epidote at depth, suggesting the presence of a heat source. As in a typical geothermal system, the rise in electrical resistivity under the conductive clay bed (products of hydrothermal alteration) may indicate the presence of a geothermal reservoir. Otherwise, no exceptional low resistivity (high conductivity) anomaly is detected at depth.